IL-32γ attenuates airway fibrosis by modulating the integrin-FAK signaling pathway in fibroblasts - Hong, Gyong Hwa (Respir Res, 2018)
BACKGROUND: Fibrosis in severe asthma often leads to irreversible organ dysfunction. However, the mechanism that regulates fibrosis remains poorly understood. Interleukin (IL)-32 plays a role in several chronic inflammatory diseases, including severe asthma. In this study, we investigated whether IL-32 is involved in fibrosis progression in the lungs. METHODS: Murine models of chronic airway inflammation induced by ovalbumin and Aspergillus melleus protease and bleomycin-induced pulmonary fibrosis were employed. We evaluated the degree of tissue fibrosis after treatment with recombinant IL-32γ (rIL-32γ). Expression of fibronectin and α-smooth muscle actin (α-SMA) was examined and the transforming growth factor (TGF)-β-related signaling pathways was evaluated in activated human lung fibroblasts (MRC-5 cells) treated with rIL-32γ. RESULTS: rIL-32γ significantly attenuated collagen deposition and α-SMA production in both mouse models. rIL-32γ inhibited the production of fibronectin and α-SMA in MRC-5 cells stimulated with TGF-β. Additionally, rIL-32γ suppressed activation of the integrin-FAK-paxillin signaling axis but had no effect on the Smad and non-Smad signaling pathways. rIL-32γ localized outside of MRC-5 cells and inhibited the interaction between integrins and the extracellular matrix without directly binding to intracellular FAK and paxillin. CONCLUSIONS: These results demonstrate that IL-32γ has anti-fibrotic effects and is a novel target for preventing fibrosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12931-018-0863-3) contains supplementary material, which is available to authorized users.